Frequency Distribution of Bacterial Vaginosis Using Nugent Score and Culture in Women with Vaginal Discharge - Naqvi, Madiha; Butt, Tariq (Infectious Diseases Journal of Pakistan, 2022)
Introduction: Accurate and timely identification of Bacterial vaginosis (BV) from high vaginal swab of high-risk patients with vaginal discharge has been found to be a cost effective measure for early diagnosis and treatment of patient, it also decreases the burden of health care cost and complications Objectives: To determine the frequency distribution of BV in women with vaginal discharge using Nugent Score and culture and evaluate agreement between these procedures. Study Design: Descriptive and Cross-sectional study Setting and Duration: This study was carried out at the Department of Microbiology, Fauji Foundation Hospital, Rawalpindi, Pakistan from July 2017 to December 2017. Subjects and Methods: All females with age more than 18 years reporting the hospital outpatient department with complaint of vaginal discharge were included in the study. Sampling technique was purposive and non-probability. At least three high vaginal swabs were taken for Gram staining, culture and wet smear for Trichomonas vegetative form. Nugent’s Score was assigned as per standard criteria. A score of 7 indicated BV. Results: Age range of patients (n=203) was from 20-80 years. Mean age was 44.58 + 10.24 (Mean + SD). In 93 patients (45.81%) Nugent Score was 7-10 whereas culture of high vaginal swabs revealed positive growth in 116 patients (57.14%). Bacterial culture was better in diagnosing BV than Nugent score (p=<0.0001). No Trichomonas was seen in all the specimens examined. Conclusion: Nugent scoring is a good, efficient and rapid method for diagnosis of BV. However, due to low positivity than that of culture negative Nugent score does not rule out the disease and needs verification with culture. Key Words: Bacterial vagnosis, Nugent Scoring, Vaginal discharge.